2018
DOI: 10.26582/k.50.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian high-level men’s volleyball

Abstract: Abstract:The present study aimed to characterize and differentiate between the predictive factors of the attacks performed by the opposite player from positions 1 and 2. The sample consisted of the observation records of 142 volleyball games of the Brazilian Men's Super-League, season 2014/2015, totaling in 8,010 actions of reception, setting and attack, with 5,965 actions from position 2 and 2,045 from position 1. The analysis of the predictive factors of the opposite player's attack, according to the positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Our primary findings revealed that traditional variables, Points (AUC = 95.2%) and Attack Efficiency (AUC = 94.3%), were the most effective predictors of victory. These results are consistent with prior research that showed the high influence of points scored upon victory (Drikos et al, 2021) and, more specifically, points from attack actions or attack efficiency (Conti et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Our primary findings revealed that traditional variables, Points (AUC = 95.2%) and Attack Efficiency (AUC = 94.3%), were the most effective predictors of victory. These results are consistent with prior research that showed the high influence of points scored upon victory (Drikos et al, 2021) and, more specifically, points from attack actions or attack efficiency (Conti et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The effect of reception is mostly recognized as a significant predictive factor of scoring points during an attack (Conti, et al, 2018, Costa, et al, 2017. For the reception effect, the relationships between reception and attack options are considered, which are classified as: a) all available attack options; b) quick attacks are possible, but they are more difficult to perform and some attack combinations are inhibited; and c) slow attack and off-court lifts are the most possible (Hurst, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The attack tempo and the attack type are also significant predictors of attack efficacy (Conti, et al, 2018;Costa, et al, 2017). The attack tempo considers the relationship between the attacker and setting and is classified as: a) first tempo attack, when the attacker is in the air or jumps during or quickly after the setting; b) second tempo attack, when the attacker takes two steps after lifting for setting; and c) third tempo attack, when the attacker takes three or more steps after lifting for setting (Costa, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the existence of a team’s recurring and systematic sequence of actions, strategies, and interactions, changes occur that depend on the balance between the teams’ skill levels (Drikos et al, 2022). In matches between teams of similar performance levels, the teams may opt for a less risky approach by focusing their attacks primarily on court positions 2 and 4, especially as the set nears its conclusion (Conti et al, 2018; Costa et al, 2017b). Thus, teams may adopt a more cautious strategy to raise their chances of winning in closely contested matches (Drikos et al, 2022; Marcelino et al, 2011).…”
Section: Introductionmentioning
confidence: 99%